2010
DOI: 10.1007/s00244-010-9629-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Genotoxicity Biomarker Responses in Grey Mullet (Mugil cephalus) From a Polluted Environment in Saronikos Gulf, Greece

Abstract: This study aimed to assess oxidative stress and genotoxicity biomarkers in grey mullet Mugil cephalus from a site receiving discharges from industrial and harbor activities and a reference site in Saronikos Gulf, Greece. Cellular antioxidant defenses, i.e., antioxidant enzyme activities (catalase, selenium [Se]-dependent glutathione peroxidase, glutathione-S-transferase) and oxidative damage, i.e., lipid peroxidation (measured as thiobarbituric acid reactive substances) were used as biomarkers of oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…For example, in a study made in the Goksu Delta (Turkey), grey mullets from the reference areas (upstream of the polluted zones) had an average MN rate of 1.26‰; the value rose to up an impressive 3.86‰ in the considered polluted areas (Ergene et al 2007). A similar trend was found also in grey mullets, but now from the Saronikos Gulf, Greece (Tsangaris et al 2011). The above considerations also apply to all the other ENMAs, and therefore warn that significantly lower values of a particular ENMA in a supposedly less polluted area should not be simplistic viewed as synonymous of having an environment that is free from genotoxicity.…”
Section: Discussionmentioning
confidence: 57%
“…For example, in a study made in the Goksu Delta (Turkey), grey mullets from the reference areas (upstream of the polluted zones) had an average MN rate of 1.26‰; the value rose to up an impressive 3.86‰ in the considered polluted areas (Ergene et al 2007). A similar trend was found also in grey mullets, but now from the Saronikos Gulf, Greece (Tsangaris et al 2011). The above considerations also apply to all the other ENMAs, and therefore warn that significantly lower values of a particular ENMA in a supposedly less polluted area should not be simplistic viewed as synonymous of having an environment that is free from genotoxicity.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, in one study different responses were reported when the same fish population were exposed to the same sediment but under either laboratory or field conditions [112]. This variability is likely due to species-specific responses [83, 101], tissue-specific responses [113], seasonal and annual variations [114] and responses to contaminants other than metals (e.g. organics [97, 98]).…”
Section: Resultsmentioning
confidence: 99%
“…In M . cephalus , hepatic CAT activity showed a significant negative response to contaminated water [72], but was also shown to be influenced by season [114]. In addition to season, the variability in CAT responses documented in field studies is likely due to salinity, location, and species [98, 102, 103, 121, 122].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some authors have suggested that ROS may be implicated in the production of high basal SCE frequencies in chromosome instability syndromes (Lee et al 1990;Therman and Susman 1993;Cinkilic et al 2009). Similarly, oxidative stress could lead to MN formations (Tsangaris et al 2010). Thus, the increases of SCE and MN rates after HgCl 2 exposure could be explained by possible prooxidant effect of this compound.…”
Section: Discussionmentioning
confidence: 97%